EFEKTIVITAS PEMERINTAH KAMPUNG DALAM PENANGAN DAN PENCEGAHAN PENYEBARAN COVID-19 TAHUN 2021 (Studi Kampung Purworejo Kecamatan Padang Ratu Kabupaten Lampung Tengah) - Lia Amala; Yonawati Yonawati; Putri Rahmaini; Marthharia Putri Utami. T (Universitas Muhammadiyah Lampung, 2022)
The village government is the spearhead of the government and is the government closest to the people, so that in handling and preventing the spread of Covid-19 which in recent years has become a national and global problem, the village government is expected to be effective in carrying out the duties of the government regions or the central government to implement the policies issued, namely the implementation of health protocols and Covid-19 vaccination activities aimed at suppressing the spread of Covid-19. Government of Purworejo Village, Padang Ratu District Lampung Tengah Regency in implementing the regulation still encountered several problems, one of which was the low implementation of health protocols in the people of Purworejo Village and the low interest of the people of Purworejo Village to carry out covid-19 vaccinations.The goal to be achieved in this study is to explore the extent of the effectiveness of the Purworejo Village Government in Handling and Preventing the Spread of Covid-19 in 2021. Researchers in this study used qualitative descriptive methods.This research resulted in data findings in the form of the Purworejo Village Government cannot be said to be effective in carrying out policies and authorities from the Central Government and Regional Governments as the spearhead in carrying out policies for implementing health protocols because there are still many people who violate health protocols and the low awareness and interest of the people of Purworejo Village to take part in the Covid-19 vaccination.Keyword: Effectiveness of the Village Government, Handling and Preventing the Spread of Covid-19.